Carcass traits of slow-growing broiler chickens: Carijó and Label Rouge (Revista de Ciências Agroveterinárias, 2023)
The objective of this study was to evaluate the carcass characteristics of male and female broilers from the free-range strains Carijó and Label Rouge. A total of 168-day-old chicks from the two strains were used and distributed in a completely randomized design, following a 2 x 2 factorial scheme. The factors considered were sex (males and females) and strain (Carijó and Label Rouge), with seven replications and 12 birds in each experimental unit (six males and six females). Significant differences were observed between the sexes (p
Keywords: slaughter; slow growth; redneck genotypes; sex